Options trading, managerial risk-taking, and brand development - Hsu, Po-Hsuan; Li, Fengfei; Nozawa, Yoshio (Journal of Banking & Finance, 2025)
This study examines how options trading influences brand development strategies by encouraging managerial risk-taking. We find that firms with higher levels of options trading tend to introduce more new trademarks, which exhibit lower citation rates from subsequent trademarks. These firms favor brand creation over extension, leading to increased brand riskiness, as evidenced by greater trademark diversity. Potential channels for these effects include increased institutional ownership by transient investors and enhanced managerial hedging opportunities. These effects are more pronounced in firms with weaker governance, managers with higher pay-risk sensitivity, younger managerial teams, and intense competition. Additionally, we observe a negative relation between unrelated brand diversification, driven by options trading, and firm value. Our findings support the notion that active options markets incentivize managers to pursue riskier brand strategies.